Effect of Na2O on Properties, Structure, and Crystallization of CaO–Al2O3‐Based Mold Fluxes. Issue 3 (28th May 2021) - Wang, Qi; Yang, Jian; Zhang, Jianqiang; Ostrovski, Oleg; Zhang, Chen; Cai, Dexiang
Abstract : This article investigates the effect of Na2 O on melting properties, viscosity, flux structure, crystallization behavior, and heat transfer of CaO–Al2 O3 ‐based mold fluxes with Na2 O concentration varied from 3.5 to 12.1 mass pct. With the increase in Na2 O content, both melting temperature and viscosity at a given temperature decrease. The Raman spectroscopy indicates that increasing the Na2 O content decreases the degree of polymerization, in line with the decrease in viscosity. Flux crystallization is studied using single hot thermocouple technology (SHTT) and double hot thermocouple technology (DHTT). The results show that flux crystallization tendency is enhanced with the increase in Na2 O content. This increase is more significant when the Na2 O content changes from 9.1 to 12.1 mass pct. X‐ray diffraction analysis of the fluxes heat treated at different temperatures reveals that the crystal precipitates vary with the flux composition and temperature. Heat transfer measurement using the IR emitter technique (IET) shows that the increase in Na2 O concentration impedes the heat transfer, in line with the increased crystallinity of the fluxes. Abstract : This article studies the effect of Na2 O on melting properties, viscosity, flux structure, crystallization behavior, and heat transfer of CaO–Al2 O3 ‐based mold fluxes with Na2 O concentration varied from 3.5 to 12.1 mass pct. Increasing Na2 O content decreases flux melting temperature, viscosity, and heat transfer, which can be attributed to the decreased degree of polymerization and the increased flux crystallization tendency.